Hubungan Peran Ayah dalam Pendidikan Seksual Terhadap Persepsi Pre Marital Seksual pada Siswa SMA di Kota Bogor - Sukma, Febi; Dayah, Siti Hairul; Riani, Yulina Eva (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Father play an important role in children’s sexual education as a basis for the formation of moral values and healthy sexual behavior in adolescents. Father’s involvement in sexual education can increase teenager’s understanding and readiness in facing challenges related to sexuality, such as pre marital sexual. The aim of this research is to determine the role of fathers in sexuality education on the attitudes of high school teenagers regarding sexuality and perceptions of pre-marital sexual relations in the city of Bogor.Method – This study uses quantitative research with a cross-sectional design, the research was conducted online with purposive random sampling on 104 high school teenagers in Bogor city. Pearson correlation test analysis was carried out with SPSS v.25. Findings – There is a significant and strong correlation between the role of communication and father’s attitude towards highschool teenagers’ perceptions of sexuality (both p value = 0.00; communication r value = 0,855; attitude r value = 0,855). There is a significant with a weak correlation between fathers' sexual education communication and teenagers' premarital sexual perceptions with p value = 0.04; r = -0,197, that the better father’s communication, the lower high school teenagers’ premarital sexual perception. Research Implications – Fathers must play a role in sexual education with good communication and attitudes with their teenagers. Prenting classes on communication and sexual education are needed for parents, especially fathers. The measurement of the father's role in this study is less detailed; it is hoped that in further research the father's role can be elaborated again in various dimensions.